1995
DOI: 10.1002/bjs.1800820144
|View full text |Cite
|
Sign up to set email alerts
|

Tumour growth stimulation after partial hepatectomy can be reduced by treatment with tumour necrosis factor α

Abstract: This study investigated whether partial hepatectomy enhances the growth of experimental liver metastases of colonic carcinoma in rats and whether treatment with recombinant human tumour necrosis factor (TNF) alpha can reduce this increased growth. Resection of 35 or 70 per cent of the liver was performed in inbred WAG rats, with sham-operated controls (five to eight animals per group). Immediately after surgery 5 x 10(5) CC531 colonic tumour cells were injected into the portal vein. After 28 days the animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…Chemotherapy was continued after each hepatectomy; this was because the growth factors involved in the hypertrophy of the remnant liver induced by the first resection can also boost the growth of the tumor tissue left in place. This phenomenon has been described after liver resection [17][18][19] and after portal embolization 20 and might be amplified by repeat surgeries. 21 Nevertheless, because regeneration is essential to the feasibility of the second-stage resection, an interval of 3 weeks was observed after each hepatectomy to minimize the inhibition of antitumor drugs on liver regeneration.…”
Section: Discussionmentioning
confidence: 91%
“…Chemotherapy was continued after each hepatectomy; this was because the growth factors involved in the hypertrophy of the remnant liver induced by the first resection can also boost the growth of the tumor tissue left in place. This phenomenon has been described after liver resection [17][18][19] and after portal embolization 20 and might be amplified by repeat surgeries. 21 Nevertheless, because regeneration is essential to the feasibility of the second-stage resection, an interval of 3 weeks was observed after each hepatectomy to minimize the inhibition of antitumor drugs on liver regeneration.…”
Section: Discussionmentioning
confidence: 91%
“…Surgical treatment is the only curative option available for patients. Previous studies suggest that removal of the primary tumour can be associated with an enhanced tumour growth of residual micro-metastases (1). Experimental animal data show that metastatic growth after liver resection is significantly accelerated in the course of hepatic regeneration (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the explanation is, perhaps, that a single liver lobe resection is a relatively minor procedure in the rat, although Slooter et al (1995) reported that resection of the left lateral lobe was enough to produce enhancement of tumour growth in the liver. Nevertheless, these findings indicate that the immunosuppressive effects of surgery or the release of growth factors was not the main factor for the increased extrahepatic spread after resection compared with laser thermotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These unwanted effects of surgery may be caused, at least partly, by immunosuppression and by the release of growth factors involved in tissue healing (Eggermont et al, 1987;Loizidou et al, 1991;Panis et al, 1992;Pollock et al, 1992;Dingemans et al, 1993;Oka et al, 1994;Slooter et al, 1995). One of the advantages of local tissue destruction is that the trauma is small compared with surgery.…”
mentioning
confidence: 99%